ANALISA USAHA TERNAK DOMBA (Ovis aries) DI KECAMATAN BATANG SERANGAN KABUPATEN LANGKAT - Kalvin Imam Inayah; Meriksa Sembiring (Bajang Institute, 2025)
The purpose of this study was to determine the effect of the type and number of sheep on economic development in Batang Sarangan District. The research method used is a direct survey method to the location or pen used as the object by collecting primary and secondary data. Primary data collection was carried out by direct observation and interviews with farmers as well as recording the existence of types and numbers and other information on each sheep farmer. Data obtained from the research field used analysis with the excel application. The collected data were analyzed using descriptive statistical analysis and the analysis results were displayed. The analysis method used in this study was the livestock condition census method for each farmer. Farmers are classified into 3 groups of farmers consisting of 1. Farmers who have > 30 sheep. 2. Farmers who have > 30 sheep and < 60 sheep and 3. Farmers who have > 60 sheep.The results obtained that farmers who have livestock > 60 (C) get greater profits and with the highest R/C with an average R/C = 2.23 and so on the smaller the number of sheep and the smaller the profit and R/C